Do asymptomatic STEC-long-term carriers need to be isolated or decolonized? New evidence from a community case study and concepts in favor of an individualized strategy - Sayk, Friedhelm; Hauswaldt, Susanne; Knobloch, Johannes K.; Rupp, Jan; Nitschke, Martin (Frontiers in Public Health, 2024)
Asymptomatic long-term carriers of Shigatoxin producing Escherichia coli (STEC) are regarded as potential source of STEC-transmission. The prevention of outbreaks via onward spread of STEC is a public health priority. Accordingly, health authorities are imposing far-reaching restrictions on asymptomatic STEC carriers in many countries. Various STEC strains may cause severe hemorrhagic colitis complicated by life-threatening hemolytic uremic syndrome (HUS), while many endemic strains have never been associated with HUS. Even though antibiotics are generally discouraged in acute diarrheal STEC infection, decolonization with short-course azithromycin appears effective and safe in long-term shedders of various pathogenic strains. However, most endemic STEC-strains have a low pathogenicity and would most likely neither warrant antibiotic decolonization therapy nor justify social exclusion policies. A risk-adapted individualized strategy might strongly attenuate the socio-economic burden and has recently been proposed by national health authorities in some European countries. This, however, mandates clarification of strain-specific pathogenicity, of the risk of human-to-human infection as well as scientific evidence of social restrictions. Moreover, placebo-controlled prospective interventions on efficacy and safety of, e.g., azithromycin for decolonization in asymptomatic long-term STEC-carriers are reasonable. In the present community case study, we report new observations in long-term shedding of various STEC strains and review the current evidence in favor of risk-adjusted concepts.